BUILDING AND ANALYSIS FOR DYNAMIC SIMULATION MODEL OF CATENARY - HU Yan; HUANG PanPan (Jixie qiangdu)
The catenary of full-compensated simple chain suspension widely used at present china railway was taken as the research object,and a dynamic simulation model of pantograph-catenary was established using the finite element method. The pantograph and catenary model were established as three dimensional flexible multibody systems,while the droppers were simulated as non-linear spring model. The coupling of pantograph-catenary system was found by the contact of pantograph and catenary. The form-finding analysis of catenary was carried out before the transient dynamic analysis of catenary. Results shows that fluctuating range of contact force between the pantograph and catenary increase gradually. In the same span,the largest force fluctuations appear in number1 and 7 droppers,tension and compression states appear in one cycle,It is more prone to damage than the rest of droppers which only bear tension force.